Ultrasensitive Quantification of Cytokine Proteins in Single Lymphocytes From Human Blood Following ex-vivo Stimulation - Saxena, Ankit; Dagur, Pradeep K.; Desai, Alisha; McCoy, John Philip (Frontiers in Immunology, 2018)
Here we demonstrate the feasibility of direct, quantitative measurement of cytokine proteins in single human CD8 lymphocytes from fresh peripheral blood of healthy donors. Cytokine-secreting cells were identified using cell surface “catch” reagents. Single cell data were obtained by sorting of cytokine-secreting cells into 96 well plates containing lysis buffer followed by analysis using ultrasensitive immunoassays for interferon gamma (IFN-γ) and tumor necrosis factor alpha (TNF-α). CD8 T cells displayed an average of 5.97 femtogram (fg) IFN-γ per cell, with a range of 1.27-15.47 fg (n=28). Per cell averages of IFN-γ in CD8 T cells showed similar results when sorting 2, 5, or 10 cells per well (6.00 fg/cell, 5.73 fg/cell, and 5.25 fg/cell, respectively) (n=28), with an average of all measurements of 5.74 fg IFN-γ per cell (SD=1.96), equal to 178,660 molecules. Surface IFN-γ negative cells revealed a mean of 1.40 fg/cell, suggesting the baseline background. Experiments from TNF-α-producing CD8 T cells showed a mean of 2.49 fg/cell TNF-α (n=28) (0.675 – 5.13 fg/cell) equals to 59,654 molecules, while sorting 2, 5, and 10 cells per well-lysate have means of 1.59 fg/cell, 1.30 fg/cell, and 1.16 fg/cell (n=28). TNF-α-negative cells showed a mean on 0.61 fg/cell (n=28). This study demonstrates that it is feasible to quantify cytokines from individual primary cells. A shift from qualitative to quantitative determinations of cytokine protein levels in single cells will permit more precise and reproducible studies of heterogeneity in the immune system and can be accomplished with readily available instrumentation.